EMPLOYEE PERFORMANCE AS A RESULT OF COMMUNICATION AND WORK ENVIRONMENT - Nina Herlina; Lia Yulia; Muhammad Zaki Rahman; Endah Puspitasari (Jurnal Ekonomi, 2023)
Study This aim For test influence communication and environment Work to performance employees at PERUMDA Tirta Giri Nata Cirebon City. Method research used _ in study This is method study quantitative. Population in study This is 180 employees of PERUMDA Tirta Giri Nata Cirebon City with sample as many as 65 employees. Data collection techniques using questionnaire and results data analysis used is analysis regression double. Research results show in a manner simultaneous influence positive and significant variable communication and environment Work to performance employee can seen from mark 7.823 > 2.76 then can concluded that Ho is rejected and Ha is accepted . It means there is influence between communication and environment Work in a manner together to performance employees at PERUMDA Tirta Giri Nata Cirebon City.